2020
DOI: 10.1101/2020.03.29.014886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-parasite tissue adhesion by a secreted type of β-1,4-glucanase in the parasitic plantPhtheirospermum japonicum

Abstract: Tissue adhesion between plant species occurs both naturally and artificially. Parasitic plants establish symbiotic relationship with host plants by adhering tissues at roots or stems. Plant grafting, on the other hand, is a widely used technique in agriculture to adhere tissues of two stems. While compatibility of tissue adhesion in plant grafting is often limited within close relatives, parasitic plants exhibit much wider compatibilities. For example, the Orobanchaceae parasitic plant Striga hermonthica is ab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These data suggest that the tissue adhesion process in parasitism is similar to that in artificial grafting, an agricultural technique used to adhere the tissues of two different stems enzymatically (Notaguchi et al ., 2020). Indeed, comparative transcriptome analysis of parasitism and grafting using P. japonicum and Arabidopsis identified GH9B3 gene homologs, encoding β‐1,4‐glucanases, as commonly upregulated during the tissue adhesion process (Kurotani et al ., 2020). Furthermore, knockdown of GH93B results in both an increased number of impaired haustoria and an increased number of grafting failures, suggesting that GH9B is an important component for both parasitism and grafting (Kurotani et al ., 2020; Notaguchi et al ., 2020).…”
Section: Host Invasionmentioning
confidence: 99%
“…These data suggest that the tissue adhesion process in parasitism is similar to that in artificial grafting, an agricultural technique used to adhere the tissues of two different stems enzymatically (Notaguchi et al ., 2020). Indeed, comparative transcriptome analysis of parasitism and grafting using P. japonicum and Arabidopsis identified GH9B3 gene homologs, encoding β‐1,4‐glucanases, as commonly upregulated during the tissue adhesion process (Kurotani et al ., 2020). Furthermore, knockdown of GH93B results in both an increased number of impaired haustoria and an increased number of grafting failures, suggesting that GH9B is an important component for both parasitism and grafting (Kurotani et al ., 2020; Notaguchi et al ., 2020).…”
Section: Host Invasionmentioning
confidence: 99%
“…We recently uncovered a key role of the GH9B3 clade of β-1,4-glucanases in cell-cell adhesion at the graft junction (Notaguchi et al 2020;Kurotani et al 2020). β-1,4-glucanases probably target cellulose in cell walls, and the overexpression of the β-1,4-glucanase gene promotes graft efficiency in Arabidopsis (Notaguchi et al 2020).…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
“…Using this system, we first showed that exogenous treatment with cellulases promotes graft adhesion. Given that numerous candidate genes related to grafting have been identified through recent transcriptome analyses (Cookson et al 2014;Liu et al 2015;Melnyk et al 2015;Li et al 2016;Chen et al 2017;Wang et al 2019;Xie et al 2019;Kurotani et al 2020;Notaguchi et al 2020 Figure 3C). In both cases, no correlation was observed between adhesive force and graft area.…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
See 2 more Smart Citations